El proceso de adaptación a la vida universitaria de estudiantes becarios durante el primer año en una universidad privada de Lima - Muñoz Guevara, Liliana Aidee (2025)
The objective of this study is to understand how scholarship students experience their adaptation process during their first year of university studies at a private university in Lima. It is a case study using educational ethnography techniques. The study population consists of 30 scholarship students enrolled in the 2023-I and 2023-II semesters in different professional degree programs. Participation in the interviews was voluntary, and the data was analyzed using Excel matrices and grounded theory. The main findings identify three main categories related to the university adaptation experience: the adaptation process, academic strategies in thematic tutorials, and the emotions experienced during this process. The testimonies contribute to the understanding that this process is not only related to the cognitive dimension but also to the social and affective dimensions. This process of student adaptation to university raises the need for an institutional policy that not only includes academic activities to close gaps but also the development of strategies for student integration and interaction from an intercultural approach.